Physical and verbal abuse, work demands, training and job satisfaction amongst aged-care employees in the home and community sector. (2nd October 2017) - Ravenswood, Katherine; Douglas, Julie; Haar, Jarrod
ABSTRACT: While the aged-care workforce undertakes a core societal role, it is a job with some challenges including working with difficult clients. This study focuses on physical and verbal abuse of aged-care employees in the home and community sector, and its relationship with work demands, training and employee outcomes. It extends the job demands–resources model into the seldom studied areas of aged-care work in the home and community sector and the issue of abuse from clients. This study uses structural equation modelling to test a mediated model with a sample of 574 aged-care employees and finds that training is highly beneficial, enhancing job satisfaction and decreasing incidences of abuse. Further, it finds that job demands have a negative impact on physical and verbal abuse, and that physical and verbal abuse has a detrimental impact on job satisfaction and turnover intentions. These findings are an important start in understanding the impact of work conditions (training, work demands, abuse) on employee outcomes (abuse, job satisfaction, intention to leave) with implications for the management of home and community aged-care employees. The findings contribute to our knowledge of physical and verbal abuse in healthcare, focusing on aged-care work in the home and community sector.